The North Atlantic Oscillation in the Azores archipelago: a Holocene high-resolution and multiproxy limnological approach - Giralt, Santiago; Hernández, Armand; Amaral-Zettler, Linda; Bao, Roberto; Birlo, S.; de Boer, E.J.; Buchaca, Teresa; Castro, D.; Carballeira, R.; Gonçalves, Vitor; Martin-Puertas, Celia; Pla Rabès, Sergi; et al. (2018)
The two main centers of action associated with North Atlantic Oscillation (NAO) climate variability occur over the Azores archipelago (high) and Iceland (low), respectively. In this context, high-resolution multiproxy characterization of lacustrine sedimentary records can provide useful insights into the NAO evolution at different temporal scales throughout the Holocene. While the Icelandic Low is relatively stable the oscillatory behavior of Azores High is relatively large and, consequently, this displacement tends to define the NAO state and impacts through time. Other atmospheric and oceanic variability modes like the East Atlantic and Scandinavian patterns, and the Atlantic Multidecadal Oscillation, also play a significant role in climate fluctuations of the European North Atlantic region. The coupling and uncoupling of these atmospheric and oceanic modes have shaped the climate variability of Southern Europe for the last 2,000 years (Sánchez-López et al., 2016 QSR, 149: 135–150), however, little is known beyond the Common Era. In order to capture the mid-to-late Holocene evolution of the NAO southern center of action and its potential interactions with other climate modes, we have recovered sediments from lakes over a large transect that spans four of the nine Azorean islands: Lagoa Caldeirão (Corvo), Lagoas Funda, Lomba, and Negra (Flores), Lagoas Caveiro and Peixinho (Pico), and Lagoas Azul and Empadadas (São Miguel). We present preliminary results from high-resolution multiproxy characterizations of these lacustrine sequences. These results suggest complex non-stationary interlinkages between the NAO and other atmospheric and oceanic climate modes on different time-scales, likely reflecting the spatial and temporal displacements of their centers of action. To fully document spatial and temporal shifts throughout the Holocene, it is crucial to study the southern NAO center of action using multiple paleorecords from this area. This research is funded through the PaleoNAO (CGL2010-15767), RapidNAO (CGL2013-40608-R) and PaleoModes (CGL2016-75281-C2) Spanish projects, and the Fundacao LUSO-Americana Peer Reviewed